Toll interacting protein gene polymorphisms in patients with systemic sclerosis: association with interstitial lung disease, outcome, and survival - Schröder, Niels; Andrä, Jitka; Knuth-Rehr, Diana; Leja, Silke; Hunzelmann, Nicolas; Moinzadeh, Pia; Frank, Konrad; Börner, Eda; Bonella, Francesco (Frontiers in Medicine, 2025)
BackgroundPulmonary fibrosis is a leading cause of death in patients with Systemic sclerosis (SSc). Single nucleotide polymorphisms (SNPs) within Toll interacting protein (TOLLIP) coding gene have been associated with progression and prognosis of Idiopathic Pulmonary Fibrosis (IPF). Aim of the present study was to investigate the association of TOLLIP SNPs with the presence, severity and outcome of interstitial lung disease (ILD) in patients with SSc.Patients and methods106 consecutive SSc patients (77 female) with (N = 53) and without ILD (N = 53) and 212 healthy controls (HC) (154 female) were genotyped for two SNPs within TOLLIP (rs3750920, rs5743890) by using TaqMan™ SNP Genotyping Assay (Thermo Fischer Scientific, USA). Disease progression was defined as ≥ 10% relative decline in FVC% pred. or ≥ 5 to < 10% decline in relative FVC% pred. and 15% relative decline in DLCO% pred. From baseline.ResultsThe TOLLIP rs5743890 minor Allele (C) was more frequent in HC than in SSc patients (41% vs. 16%, p = 0.021). The homozygote alleles of rs5743890 were significantly overrepresented in SSc patients compared to HC (84% vs. 71%, p = 0.008). Among SSc patients with ILD, those carrying the rs5743890 T/C genotype had a tendentially worse survival (158 vs. 213 months, p = 0.162) and a significantly higher rate of disease progression (66% vs. 22%, p = 0.003) compared to homozygotes. The rs5743890 minor allele C was an independent predictor of progression after adjustment for a number of covariates (HR 4.29, 95% CI 1.48–12.48, p = 0.008). Moreover, the TC haplotype appeared to be an even stronger predictor of progression than rs5743890 alone (HR 7.71, 95% CI 1.79–33.12, p = 0.006).ConclusionTOLLIP SNP rs5743890 genotype distribution seems to differ in SSc patients compared to HC. The rs5743890 heterozygote genotype and the TC haplotype may be associated with an increased risk of progression in patients with SSc-ILD.